2017
DOI: 10.1026/0932-4089/a000253
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Well-Being by Teaching Employees How to Segment Their Life Domains

Abstract: Abstract. Changes in technology, economy, and demography have generated today’s mobile and flexible workplace. These aspects, while leading to more permeable boundaries, render it more difficult to manage the boundaries between life domains. We conducted a quasi-experimental study to evaluate the effects of an intervention teaching mindfulness as a cognitive–emotional segmentation strategy to promote well-being. In all, 191 employees participated in the 3-week online self-training intervention and completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 75 publications
1
17
1
2
Order By: Relevance
“…The MBI teaches mindfulness as a cognitive-emotional segmentation strategy for detaching from work. We build on research showing that the MBI is effective for encouraging work-life balance (Michel et al, 2014) and improve well-being (Rexroth, Michel, & Bosch, 2017). However, we extend that research by investigating how intervention effects unfold over time and whether segmentation preferences moderate the effects.…”
mentioning
confidence: 99%
“…The MBI teaches mindfulness as a cognitive-emotional segmentation strategy for detaching from work. We build on research showing that the MBI is effective for encouraging work-life balance (Michel et al, 2014) and improve well-being (Rexroth, Michel, & Bosch, 2017). However, we extend that research by investigating how intervention effects unfold over time and whether segmentation preferences moderate the effects.…”
mentioning
confidence: 99%
“…In den vergangenen Jahren hat die Forschung untersucht, welche Strategien helfen, Grenzen zwischen Lebensbereichen zu managen [7,8]. Diese Strategien sind leicht erlernbare verhaltensorientierte Maßnahmen und können in Psychotherapie und Beratung eingesetzt werden.…”
Section: Umgang Mit Verschwommenen Grenzen Zwischen Den Lebensbereichenunclassified
“…Achtsamkeit kann als kognitiv-emotionale Segmentationsstrategie eingesetzt werden, da sie dazu beiträgt, Work-Life-Balance, Erholung und Lebenszufriedenheit zu fördern sowie negativen Affekt und emotionale Erschöpfung zu reduzieren [8,9] (Infobox 3).…”
Section: Aus Der Praxisunclassified
“…Diminishing boundaries between work and private life as a result of working time and workplace flexibility have triggered research on employees' preferences regarding the segmentation or integration of life domains (Ammons 2013). While it has repeatedly been found that behavior aimed at the segmentation of work and private life domains is related to favorable work-life outcomes (e.g., Kreiner 2006;Michel et al 2015;Rexroth et al 2017), research on segmentation preferences is not that consistent. Findings so far suggest that segmentation preferences are not directly related to work-life outcomes-except for psychological work-family conflict, indicating a preoccupation with one role while being in the other (Allen et al 2014;Park and Jex 2011).…”
Section: Introductionmentioning
confidence: 99%